Ecocosmism as a Measurement of a Ukrainian Nation Outlook (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the question of language realization of an idea of ecocosmism in a Ukrainian culture, forming of ecological ethics of the person by the expressive means of language. To the category of concept, which is able to inspire a reaction of cultural character within the language users, we refer the concept Nature. Structural-semantic peculiarities of statement-ascribing, statement-appraisal and aesthetic sayings are determined and analyzed.
Keywords: culture; mentality; ecocosmism; the language of ethics; concept